2005
DOI: 10.1183/09031936.05.00047804
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor is released by IL-1  and induces hyperresponsiveness of the human isolated bronchus

Abstract: Nerve growth factor (NGF) is a neurotrophic factor essential for the development and survival of neurons, and is also an important mediator of inflammation. It is released by airway cells stimulated by interleukin (IL)-1b. As IL-1b induces airway hyperresponsiveness (AHR) to the tachykinin NK-1 receptor agonist [Sar 9 ,Met(O 2 ) 11 ]-substance P in human isolated bronchi, the aim of this study was to determine whether IL-1b was able to induce NGF release from isolated bronchi, and whether NGF might partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…The C57BL/6 mice, which are often reported to have more of a Th1 bias as compared with the Th2 bias of BALB/c mice (19,20), have higher levels of IL-5 and IL-13 ( Figure 3) in the BALF, which is followed by higher numbers of eosinophils later in the inflammatory response. Nerve growth factor, although not strictly a cytokine, has been proposed as a mediator of AHR in airway tissue (21,22). We found that it was sharply elevated in the 14-to 24-day time period after inoculation in both strains of mice ( Figure 4A), which may imply a role in the later onset of AHR.…”
Section: The General Immune Response To Pneumocystis Is Strain Specificmentioning
confidence: 56%
“…The C57BL/6 mice, which are often reported to have more of a Th1 bias as compared with the Th2 bias of BALB/c mice (19,20), have higher levels of IL-5 and IL-13 ( Figure 3) in the BALF, which is followed by higher numbers of eosinophils later in the inflammatory response. Nerve growth factor, although not strictly a cytokine, has been proposed as a mediator of AHR in airway tissue (21,22). We found that it was sharply elevated in the 14-to 24-day time period after inoculation in both strains of mice ( Figure 4A), which may imply a role in the later onset of AHR.…”
Section: The General Immune Response To Pneumocystis Is Strain Specificmentioning
confidence: 56%
“…In addition, AHR is observed after in vitro NGF pre-treatment of guinea pig (de Vries et al, 2001), ferret (Wu & Dey, 2006) or human bronchi (Frossard et al, 2005). AHR is reduced in vivo after administration of a pan-Trk receptor decoy in a mouse model of asthma (Nassenstein et al, 2006), or of the TrkA kinase inhibitor K252a in a guinea pig model of asthma (de Vries et al, 2006), thus showing involvement of the TrkA receptor in NGF-induced AHR.…”
Section: Ngf Trka and Tissue Hyperresponsiveness 521 Asthmamentioning
confidence: 87%
“…Various visceral epithelia are known to produce neurotrophins which were initially speculated to regulate tissue innervation [32] and autocrine functions of neurotrophins are increasingly being described. For example, NGF production is increased during inflammatory processes that are accompanied by epithelium damage in asthma [17,33], infections [34] and sarcoidosis [35].…”
Section: Discussionmentioning
confidence: 99%